ChemInform Abstract: A 2‐Iodobenzamide Catalyst for Oxidation of Alcohols at Room Temperature. Issue 45 (23rd October 2014) - Yakura, Takayuki; Yamada, Akihiro; Noda, Narumi; Fujiwara, Tomoya; Nambu, Hisanori
Abstract Treatment of primary and secondary alcohols with a catalytic amount of iodobenzamide in the presence of oxone yields the corresponding carbonyl compounds.